Transforming personal reality: a descriptive study of the experiences of women diagnosed initially with advanced stage breast cancer - Tapper, Viva Jane (My University, 2000)
The purpose of this study was to discover and elaborate the illness-related experiences and processes reported by a homogenous sample of women whom were initially diagnosed with advanced stage breast cancer (BrCa) and to generate an explanatory model of these processes and experiences.Flowing from a pragmatic paradigm, within a symbolic interactionist perspective, grounded theory methodology was utilized. Eight women were interviewed in person on three occasions over time, and when possible, various stages of the disease trajectory, to capture the course and nature of the processes in which these women were engaged.The core category that explained the process women with advanced stage breast cancer endured was Transforming Personal Reality. Within the context of having their breast cancer medically discovered, diagnosed, and treated, women experienced four psychodynamic processes: Realizing, Processing, Battling, and Being. The outcome of a circular pattern of the dawning of awareness, connecting with a provider, following on their instincts, and perceiving urgency, the diagnosis of advanced stage BrCa horribly imploded the woman's world. Their breast cancer diagnosis signaled an end to the reality they had perceived before, and they entered a process of reconstructing a reality that fit their experiences. Gathering evidence related to the significance of the diagnosis, and gathering steam for the battle to be waged for survival, these women fought with all their hearts and souls to get through the treatment, and out the other end. Blasted by chemicals, radiation, and carved by surgeon's knives, the women in this study endured physical pain, significant side effects, and bore emotional and psychological scars. They not only endured physically, but they also entered a psychological and spiritual process that required reflection on personal meaning and purpose, deciding how they were going to deal with their existence and a reawakening to their life in the present. The hallmark of living with advanced stage BrCa is the transformative process that each woman experienced in which where lives were forever changed.The discussion chapter includes interpretation of results, methodological recommendations, clinical implications, and future directions for research.
Thesis (Ph. D.)--University of Washington, 2000
Keywords: Theses--Nursing